Supervisory predictive control and on-line set-point optimization - Tatjewski, Piotr (Zielona Góra: Uniwersytet Zielonogórski)
The subject of this paper is to discuss selected effective known and novel structures for advanced process control and optimization. The role and techniques of model-based predictive control (MPC) in a supervisory (advanced) control layer are first shortly discussed. The emphasis is put on algorithm efficiency for nonlinear processes and on treating uncertainty in process models, with two solutions presented: the structure of nonlinear prediction and successive linearizations for nonlinear control, and a novel algorithm based on fast model selection to cope with process uncertaint
Keywords: predictive control; nonlinear control; linearization; model uncertainty; constrained control; set-point optimization